Genetic variability of pure Pseudoplatystoma corruscans and Pseudoplatystoma reticulatum individuals in the Paraná and Paraguay River basins - Vaini, Jussara Oliveira; do Amaral Crispim, Bruno; dos Santos Silva, Danielly Beraldo [UNESP]; Benites, Celso; Russo, Marcia Regina; Grisolia, Alexéia Barufatti (Springer Nature, 2016)
The presence of interspecific hybrid surubim (Pseudoplatystoma corruscans × Pseudoplatystoma reticulatum) in natural environments can put at risk the existence of the pure parental lineages. The aim of this study was to characterize the genetic variability of pure Pseudoplatystoma corruscans and Pseudoplatystoma reticulatum individuals from rivers in the Paraná and Paraguay basins in Brazil. Seventy-six pure individuals of P. corruscans and 16 of P. reticulatum were evaluated with six microsatellite loci for both species, along with one species-specific locus each for P. corruscans and P. reticulatum. Loss of heterozygosity was confirmed, and preservation measures for P. corruscans and P. reticulatum are needed in order not to lose further genetic variation. In addition, we confirmed that these markers are useful for the management of pure stocks in natural environments, for fish breeding, and in genetic conservation and improvement programs for these species.
Keywords: Conservation; Crossbreeding; Fish; Microsatellite; Natural environment